Pengembangan Smart Application Translation Aneka Bahasa Sulawesi Berbasis Android - Maslan - Maslan; Yana Setiono; Faizal Alfazri (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2016)
The Indonesian people have diverse tribes. Similarly, the regional language that is widespread in Indonesia, each of the tribes in Indonesia have different languages included in South Sulawesi. The number of local and foreign travelers to visit tourist attractions in the city, so that will indirectly communicate with the locals at the time of tourist visits. This research aims to develop smart applications translators Indonesian to Sulawesi region based on Android. This application can translate the three regional languages, namely the language Konjo, makasar and Bugis. The method used is research development by using the Linear Sequential Model. Applications can run well and have gone through the testing phase by inserting a vocabulary of 100 vocabularies for each language area. So that these applications can be used by people in Indonesia who can get through the Google Play Store